TRAINING BIMBINGAN KEBAHAGIAAN DALAM PERSPEKTIF AL-GHAZALI DAN RELEVANSINYA TERHADAP ALIENASI MANUSIA MODERN DI MAJLIS TAKLIM MUSLIMAT BEKASI - Ali Nurdin; Mohamad Zaenal Arifin; Asep Muksin; Ahmad Kamaludin; Mildanti Mildanti; Otong Surahman (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This study tries to uncover one of the thoughts of the Muslim philosopher Al-Imam Al-Ghazali with the concept of happiness and its relevance to the situation of alienation of modern society today, or what is called alienation. This study describes that the true happiness in Al-Ghazali's thought is the happiness of the hereafter, while worldly happiness is only a metaphorical happiness. And the peak of happiness can be achieved by someone when it has reached the ma'rifat of Allah. The ma'rifatullah process begins with tazkiyyatu al-Nafs, muhâsabatu al-Nafs, and ends with taqwiyyatu al-Nafs. The method used in this research is a qualitative analysis method through library research with an interpretive descriptive approach. The temporary conclusion of this study shows that Al-Ghazali's concept of happiness will be the answer to the problem of alienation that underlies modern humans today by strengthening the arid soul, giving meaning and direction to life with the virtues of wisdom, sajâ'ah, iffah, and 'adâlah